URGENSI PENCATATAN NIKAH DALAM PENCEGAHAN STUNTING SERTA POLA ASUH ANAK DENGAN PEMANFAATAN MEDIA SOSIAL UNTUK KESEJAHTERAAN EKONOMI KELUARGA - H Sihite, SP.,MM, Tiurlina; Sucipto, Sucipto; Danu Irwan Zaelani Matondang, Danu Irwan; Hesty Amelia Gultom, Hesty; Furi Windari, Furi (Jurnal Masyarakat Indonesia (Jumas), 2025)
Marriage registration plays an important role in preventing stunting, a condition of chronic malnutrition that affects children's growth. It provides various benefits, such as ensuring the health status and age of prospective couples, providing access to health information and education, recording data for health and nutrition assistance, supporting better pregnancy planning, and facilitating the monitoring of maternal and child health by healthcare workers. Registered couples are easier to monitor for prenatal check-ups and child growth tracking, allowing potential nutritional issues that may cause stunting to be detected and addressed earlier. Overall, marriage registration is an important first step to ensure that new families begin their journey with sufficient knowledge and support, particularly in health and nutrition aspects, minimizing the risk of stunting in children. With proper parenting and the wise use of social media, parents can not only focus on their child’s growth and development but also create opportunities to enhance the family’s economic well-being.